Study on the Suitability and Impact of the Policy of Increasing Excise Tax on Rolling Tobacco - patchimnan, attakrit; patchimnan, mana (King Prajadhipok’s Institute Journal, 2021)
Econometric research helps for designing a suitable tobacco tax policy, and leads to policy guidelines that reflect actual benefits for government revenue collection. The study concludes that effective policy strategy must take into account only the increasing tax levels in order to diminish consumption. For example, tobacco products for consumption has not decreased at the current tax level are considered urgent subjects of policy. The design of the optimal tax rate may require use of GDP as a management tool. In addition, national income affects the amount of tobacco sold; therefore, when the country has a higher national income, the government needs to continually increase the tax rate as long as consumption declines at the optimal level.